Gender Categories as Dual‐Character Concepts?. Issue 5 (21st May 2021) - Guo, Cai; Dweck, Carol S.; Markman, Ellen M.
Abstract: Seminal work by Knobe, Prasada, and Newman (2013) distinguished a set of concepts, which they named "dual‐character concepts." Unlike traditional concepts, they require two distinct criteria for determining category membership. For example, the prototypical dual‐character concept "artist" has both a concrete dimension of artistic skills, and an abstract dimension of aesthetic sensibility and values. Therefore, someone can be a good artist on the concrete dimension but not truly an artist on the abstract dimension. Does this analysis capture people's understanding of cornerstone social categories, such as gender, around which society and everyday life have traditionally been organized? Gender, too, may be conceived as having not only a concrete dimension but also a distinct dimension of abstract norms and values. As with dual‐character concepts, violations of abstract norms and values may result in someone being judged as not truly a man/woman. Here, we provide the first empirical assessment of applying the dual‐character framework to people's conception of gender. We found that, on some measures that primarily relied on metalinguistic cues, gender concepts did indeed resemble dual‐character concepts. However, on other measures that depicted transgressions of traditional gender norms, neither "man" nor "woman" appeared dual‐character‐like, in that participants did not disqualify people from being truly a man or truly a woman. In a series of follow‐up studies, we examined whether moral norms have come to replace gender role norms for the abstract dimension. Implications for the evolution of concepts and categories are explored.